Pengaruh Faktor-Faktor Pelatihan Terhadap Prestasi Kerja Pegawai Pada Dinas Tanaman Pangan, Holtikultura Dan Perkebunan Kabupaten Malaka - Guido Krisantus Nahak; Rahmat Laan; Hanifa Djakaria (Jurnal Manajemen, 2019)
This study aims to analyze the partial and simultaneous influence of trainingfactors on employee work performance. The research sample of 70employees, with the sampling method using saturated sample techniques. Themain instrument of data collection is a questionnaire. Data were analyzedusing multiple regression. The results showed that partially the trainingfactors consisting of training instructors, training participants, trainingmethods, and training objectives, significantly influence employeeperformance. Simultaneously these factors also have a significant effect onwork performance. The training method is the factor that has the mostdominant influence on employee work performance.